Online Customer Experience Leads to Loyalty via Customer Engagement: Moderating Role of Value Co-creation - Ahmad, Farooq; Mustafa, Khurram; Hamid, Syed Ali Raza; Khawaja, Kausar Fiaz; Zada, Shagufta; Jamil, Saqib; Qaisar, Muhammad Nawaz; Vega-Muñoz, Alejandro; Contreras-Barraza, Nicolás; Anwer, Naveed (Frontiers in Psychology, 2022)
With the increasing growth of online shopping, businesses are intertwining to establish new shopping antecedents. Customer experience has steadily become the most important source of retailers’ long-term competitive advantage via difference. To preserve long-term and sustained consumer loyalty, retailers must continually improve the customer experiences. This study presents a framework for online retailing in a digital environment called the Online Customer Experience-Engagement Context model in the presence of value co-creation (VCC). Data was gathered from 189 people who purchased products online. For additional analysis, testing the hypothesis, and model construction, SPSS 26 and Smart-PLS were used. The data was then evaluated further using descriptive statistics, path analysis, measurement, and structural model. The findings show that the online customer experience (measured as shopping environment, shopping procedure, staff service experience, and product experience) substantially influenced customer engagement, which improved customer loyalty. The VCC strengthened the link between online customer experience and customer engagement. It suggests that including consumers in co-creating a delightful online customer experience from time to time may be a valuable strategy for online retailers to increase customer engagement and loyalty. To create an overarching outcome, information integration theory (IIT), multi-attribute utility theory (MAUT), and the attitude-behavior-context theory (ABC) theories are converged to explain the proposed model in the study.